PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI UPT LABORATORIUM KESEHATAN DAN LINGKUNGAN DINAS KESEHATAN PROVINSI RIAU - Aria, Decky; Hendriani, Susi; Wijaya, Errin Yani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research held in Unit Pelaksana Teknis (UPT) LaboratoriumKesehatan & Lingkungan Dinas Kesehatan Riau Province. This research held in order to analyze the influence of organization culture and leadership to employees performance. Population are all employees, consist of 45 people. Considering the number limitation so sampling method used is census that covers all employee as the respondents. Variables used are organization culture and leadership as independent and performance as dependent. Data analyzed by using descriptive analysis and multiple regression analysis by using SPSS 17 for windows. Result of this study shows that both organization culture and leadership significantly influence, either in simultenously or partially, to employees performance. Organization culture is the dominant factor that influence employees performance compared to influence given by leadership factor. It is recommended to company to enhance organization culture implementation, particularly on innovation and cooperative ability aspect. Leadership promotion needs to involve employees’ aspiration and all unit leaders are suggested to directly show good behavior to all employees.Keywords: Organization Culture, Leadership and Performance